Sightless Students and Inclusive Classroom: A Case of a Sightless Girl - Upadhayay, Giri Raj (Prāgyik Prabāha, 2023)
This study focuses on the classroom practices of a school run by the principles of inclusive policy and its strategies to treat sightless students in the inclusive classroom. The study aimed at exploring the classroom conditions of inclusiveness in a diverse classroom context. In order to attain the objectives, a case study research method was employed in which the data was collected from poor and sightless students who were purposively selected. The required information was collected through interviews and the observation of classroom context. The thematic analysis approach was used to analyze and interpret the data. Accordingly, the recorded data was transcribed at first, then the codes were developed and then the codes were organized into the themes, and ultimately the themes were discussed with reference to the data from the interview and observation. The findings of the study entailed that the sightless student had difficulty to adjust herself in the classroom, she felt that the instructional strategy and the classroom setting was not inclusive as it was expected to be and the classroom was not inclusive though it said to be like that. The problematic students, especially sightless students felt a sort of discrimination in the teaching strategy of their teachers. The study concludes that though the policy of inclusive education and classroom is principally good, the implementation part is quite poor in our diverse classrooms.